Dinamika Kode Etik Jurnalistik Produksi Berita Audio : Kajian Literatur Terhadap Praktik Media Audio - Maria Erica Widyadini Fernanda; Melati Budi Srikandi; Jonathan Jacob Paul Latupeirissa; I Nyoman Indra Kumara (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine how journalistic ethical principles are applied, interpreted, and challenged within audio-based news production. It specifically explores the influence of digital transformation on the professionalism, accuracy, and credibility of audio journalism, including radio news and podcast-based reporting. The research adopts a thematic literature review approach by analyzing books, peer-reviewed journal articles, ethical frameworks, and international media guidelines published in the last five years. The collected literature was categorized into themes related to ethical principles, audio narration techniques, verification challenges, and digital media practices. Thematic synthesis was used to identify patterns, recurring issues, and gaps within current ethical implementations. Findings indicate that audio journalism presents unique ethical vulnerabilities, such as the potential manipulation of audience perception through tone, sound effects, and music. The absence of visual evidence complicates verification processes, increasing the risk of misinformation. The study also shows that independent audio producers often lack adherence to formal ethical standards, creating inconsistencies in accuracy, transparency, and narrative balance. These challenges demonstrate the need for clearer ethical guidelines tailored to audio formats. The study concludes that conventional journalism ethics must be adapted to address the specific narrative and technical characteristics of audio media. Strengthening editorial oversight, establishing transparent verification procedures, and promoting responsible use of sound elements are essential to ensure credibility and maintain public trust. Developing specialized ethical frameworks for audio journalism is therefore critical in the digital era. Materials and Methods. The research adopts a thematic literature review approach by analyzing books, peer-reviewed journal articles, ethical frameworks, and international media guidelines published in the last five years. The collected literature was categorized into themes related to ethical principles, audio narration techniques, verification challenges, and digital media practices. Thematic synthesis was used to identify patterns, recurring issues, and gaps within current ethical implementations. Results. Findings indicate that audio journalism presents unique ethical vulnerabilities, such as the potential manipulation of audience perception through tone, sound effects, and music. The absence of visual evidence complicates verification processes, increasing the risk of misinformation. The study also shows that independent audio producers often lack adherence to formal ethical standards, creating inconsistencies in accuracy, transparency, and narrative balance. These challenges demonstrate the need for clearer ethical guidelines tailored to audio formats. Conclusions. The study concludes that conventional journalism ethics must be adapted to address the specific narrative and technical characteristics of audio media. Strengthening editorial oversight, establishing transparent verification procedures, and promoting responsible use of sound elements are essential to ensure credibility and maintain public trust. Developing specialized ethical frameworks for audio journalism is therefore critical in the digital era. Keywords: audio journalism, media ethics, ethical standards, digital news production, podcast journalism, verification challenges